THE SIGNIFICANCE OF RATIFYING INTERNATIONAL LAWS AND RESOLUTIONS ON ANTI-CORRUPTION IN UZBEKISTAN: ECONOMIC-POLITICAL AND SOCIO-LEGAL MECHANISMS - Mustafayev J. Sh.; Boliyev Ravshan Akmal o’g’li (Лучшие интеллектуальные исследования, 2024)
Abstract: The article is devoted to an analysis of legal acts of the Republic of Uzbekistan on counteraction against corruption. The article provides the classification and review of the anti-corruption legislation of Uzbekistan. The article also deliberates about the measures taken by Uzbekistan to implement relevant international legal standards into the national legal system[1]. [1] https://lup.lub.lu.se/search/files/70261479/REVIEW_OF_ANTI_CORRUPTION_LEGISLATION_OF_THE_REPUBLIC_OF_UZBEKISTAN_AND_ISSUES_OF_ITS_FURTHER_IMPROVEMENT.pdf